Development of a compact cavity BPM for real-time monitoring of clinical proton beams at HUST-PTF - Li, Jiqing; Lu, Yuexin; Li, Jiapeng; Wang, Jian; Liu, Zhengzheng; Meshkov, Oleg; Yang, Jinfeng; Fan, Kuanjun (Frontiers in Oncology, 2025)
IntroductionTo ensure the safety and efficacy of precise proton therapy, real-time and non-intrusive monitoring of the clinical beam position is essential. However, in cyclotron-based proton therapy facilities, clinical proton beams with low repetition frequency and exceptionally low intensity due to the Energy Selection Systems (ESS), pose considerable challenges for accurate online beam diagnostics. Conventional non-interceptive beam diagnostic devices lack the sensitivity required to detect such weak beams with sufficient precision.MethodsThis paper presents an innovative solution to this challenge: an off-centerrectangular cavity Beam Position Monitor (BPM) with dielectric loading. This novel design achieves remarkable position sensitivity while maintaining compact transverse dimensions of 500×250×100 mm.ResultsA prototype of this cavity has been fabricated and tested offline. Experimental results demonstrate that, within the clinical treatment energy range, the BPM achieves minimum beam position measurement sensitivities of 0.49 nV/mm at 70 MeV and 17.12 nV/mm at 230 MeV. In addition to enabling online beam position monitoring without disturbing the beam path, which ensures real-time beam orbit feedback correction with submillimeter stability (± 0.5 mm).DiscussionIn addition to monitoring beam positions for precise control of the beam orbit, the BPMs could serve additional functions to enhance proton therapy—such as enabling beam energy verification through the phase of the BPM signal.